Comparison of high-performance thin layer chromatography/UV-densitometry and UV-derivative spectrophotometry for the determination of trimetazidine in pharmaceutical formulations - Gackowski Marcin; Koba Marcin; Mądra-Gackowska Katarzyna; Kruszewski Stefan (Acta Pharmaceutica)
New methods for assaying trimetazidine dihydrochloride on the basis of thin layer chromatography and spectrophotometry are proposed and compared in the paper. In HPTLC/UV-densitometry, separation is achieved by using a mobile phase composed of ammonia-methanol (30:70, V/V) on silica gel HPTLC plates F254. Quantification using a non-linear calibration curve is accomplished by densito-metric detection at 230 nm. Derivative spectrophotometric determination of trimetazidine dihydrochloride is carried out from the fourth derivative of the absorbance at 233 nm in peak-zero mode. Statistical comparison led to the conclusion that there is no significant difference between the two studied methods and, moreover, that they demonstrate satisfactory accuracy and precision for routine applications.